2005
DOI: 10.1634/stemcells.2005-0058
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Differentiation of Embryonic Stem Cells into Insulin-Secreting Cells by Fetal Soluble Factors

Abstract: Cell signals produced during pancreas embryogenesis regulate pancreatic differentiation. We show that the developing pancreas releases soluble factors responsible for in vitro endocrine pancreatic differentiation from embryonic stem cells (ESCs). A mouse D3 ESC line was transfected with a human insulin promoter/␤geo/phosphoglycerate kinase-hygromycin-resistant construct. To direct differentiation, cells were cultured for 7 days to form embryoid bodies and then plated for an additional 7 days. During this 14-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 18 publications
1
65
1
Order By: Relevance
“…It was also shown that differentiated cells do not form teratomas (4,5) and they mature 30 days after transplantation (4). Subsequently, in vitro differentiation protocols for human embryonic stem cells (hESCs) or induced pluripotent stem cells succeeded in generating definitive endoderm (6)(7)(8). Numerous protocols have been published that have yielded insulin-producing cells from pluripotent stem cells (9)(10)(11).…”
Section: )mentioning
confidence: 99%
“…It was also shown that differentiated cells do not form teratomas (4,5) and they mature 30 days after transplantation (4). Subsequently, in vitro differentiation protocols for human embryonic stem cells (hESCs) or induced pluripotent stem cells succeeded in generating definitive endoderm (6)(7)(8). Numerous protocols have been published that have yielded insulin-producing cells from pluripotent stem cells (9)(10)(11).…”
Section: )mentioning
confidence: 99%
“…Inherent variability in the behavior of individual ESC lines, in conjunction with these responses in the absence or presence of serum, could explain these results. Studies that identify the molecules released by developing pancreas could help to determine the main factors needed in ESC-IPC differentiation in vitro (Vaca, Martin et al 2006). These studies could also be applied in the development of synthetic molecules, such as indolactam V, IDE1 or IDE2, for easier production and control of murine and human ESC-IPC differentiation (Borowiak, Maehr et al 2009;Chen, Borowiak et al 2009).…”
Section: Differentiation Of Embryonic Stem Cells Into Insulin Producimentioning
confidence: 99%
“…Studies have also recognized karyotypic instability of long term hESC cultures with recurrent chromosomal gain characteristic of some germ cell tumours (Draper et al 2004). These concerns are not alleviated by standard laboratory transplantation experiments; the length of time used to assess cell replacement in diabetic mice is too short for adequate appreciation of tumour risk in patients (Vaca et al 2006). …”
Section: Potential Problems Inherent To the Starting Escsmentioning
confidence: 99%